Optimization and control of a large-scale solar chimney power plant - Pretorius, Johannes Petrus (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Mechanical and Mechatronic Engineering))-- University of Stellenbosch, 2007.